Development of A Small-Scale Vortex-Induced Wind Turbine - Samsudin, Mohd Izzat Syahmi; Mohd, Sofian (Progress in Aerospace and Aviation Technology, 2022)
Over the last several years, there has been a significant and encouraging interest in the generation of power from wind, however, a massive wind turbine can only operate in a high wind speed condition. Vortex bladeless wind turbine is a completely new idea of wind turbine with a different mode of operation. It is designed to operate in a low wind speed condition which is a preferable option for areas with such conditions as in Malaysia. This study aims to develop and evaluate a functional prototype of a vortex bladeless wind turbine that can be used to harvest wind energy in a low wind speed condition. A vortex bladeless wind turbine is fabricated based on existing research on the principle of vortex shedding phenomenon. It is built in a cylindrical shape with approximately 2m in height measuring from the base to the top of the mast and 0.2m in diameter. The structure of a bladeless wind turbine is a flexible cylindrical mast over the setup that captures potential forms of energy from moving airstreams and uses a vortex-induced vibration (VIV) mechanism to produce vibration in the structure. The testing was done by using a wind tunnel’s exhaust that produced 1m/s to 10m/s of airflow which simulates a low to medium wind speed condition. The vibration is turned into electrical energy, using a power generating system like an electromagnetic induction mechanism. The analysis of the results is based on numerous data points gathered during the testing, including the frequency of oscillation, vortex shedding and natural frequency, and resonance parameter. Through the investigation, the results show that the phenomena of induced vibration were working at even critically low to moderate wind speeds, where standard and conventional wind turbines may fail to produce the desired outcomes. On this basis, it is confirmed that the prototype of vortex bladeless wind turbine is working properly in harvesting wind energy though several improvements need to be made.